2016
DOI: 10.1016/j.neuron.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Population-Level Representation of a Temporal Sequence Underlying Song Production in the Zebra Finch

Abstract: SUMMARY The zebra finch brain features a set of clearly defined and hierarchically arranged motor nuclei that are selectively responsible for producing singing behavior. One of these regions, a critical forebrain structure called HVC, contains premotor neurons that are active at precise timepoints during song production. However, the neural representation of this behavior at a population level remains elusive. We used 2-photon microscopy to monitor ensemble activity during singing, integrating across multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
156
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(164 citation statements)
references
References 62 publications
7
156
1
Order By: Relevance
“…A hallmark of HVC RA cells is their remarkable capacity to fire action potentials in an ultra-sparse and sequential, clock-like manner during singing (Hahnloser et al, 2002; Lynch et al, 2016; Picardo et al, 2016). The simulation and intracellular recording methods used here suggest that this ultra-sparse action potential activity is generated from recurrent, high frequency (30-60 Hz) and synchronous synaptic inputs rather than simply from a local excitatory chain mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…A hallmark of HVC RA cells is their remarkable capacity to fire action potentials in an ultra-sparse and sequential, clock-like manner during singing (Hahnloser et al, 2002; Lynch et al, 2016; Picardo et al, 2016). The simulation and intracellular recording methods used here suggest that this ultra-sparse action potential activity is generated from recurrent, high frequency (30-60 Hz) and synchronous synaptic inputs rather than simply from a local excitatory chain mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that estrogens acting within HVC regulate song stereotypy (Meitzen et al, 2007). Aromatase (AROM) expression has been found within the POM in multiple songbirds, including canaries (Shen et al, 1995;Fusani et al, 2000), whereas AROM protein (in the absence of detectable AROM mRNA) has been found within presynaptic boutons within HVC in zebra finches (Peterson et al, 2005). Therefore, in addition to the potential actions of estrogens of a gonadal origin acting in the POM and HVC to regulate song, actions of estrogens generated from testosterone within these nuclei is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that neural activity/hormone action in one region can influence morphological or neurophysiology characteristics in downstream or upstream brain regions (Brenowitz and Lent, 2002;Meitzen et al, 2007;Larson et al, 2013;Brenowitz, 2015;Alward et al, 2016c), which could affect control of song. All song features listed in italics are predicted to be controlled by androgens and/or estrogens based on the results of past studies (Spiro et al, 1999;Long and Fee, 2008;Picardo et al, 2016). HVC is colored as a gradient to represent the topographical nature of its functions: lateral HVC controls aspects of syllable usage, whereas medial HVC controls aspects of syntax (Basista et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult zebra finches (Taeniopygia guttata) sing renditions of a stereotyped motif (a sequence of 3-10 syllables), whose temporal and/or motor structure is thought to be encoded in the activities of two major types of HVC neurons (Fig. 1a) [8][9][10][11][12][13] . We implanted 16/32 site Si-probes in male, adult zebra finches and recorded simultaneously their song and neural activity in HVC; then we used these data to train a long-short-term memory network (LSTM 5 ) to translate neural activity directly onto song.…”
mentioning
confidence: 99%